MISSIO DEI SEBAGAI PERSEKUTUAN RELASIONAL: REFLEKSI MISIOLOGIS DARI YOHANES 17:20–21 BAGI GEREJA MASA KINI - Paulus Purwoto; Kalis Stevanus; Yunianto Yunianto (Sekolah Tinggi Teologi Arastamar Bengkulu, 2026)
This paper re-examines the concept of Missio Dei as a relational fellowship, starting from a theological study of John 17:20–21. In practice, the understanding of the church's mission is often reduced to mere programmatic activities or efforts to expand church institutions. This perspective has the potential to ignore the relational dimension that is actually the main foundation of the mission itself. This research uses a qualitative approach with theological analysis methods. The review process is carried out through the study of relevant literature and exposition of the biblical text, especially John 17:20–21. The results of the analysis show that John 17:20–21 emphasizes that the sending of the disciples is a continuation of the existing relationship between the Father and the Son. Missio Dei is essentially the church's participation in the relational fellowship of the Triune God. The church is not only called to carry out various mission activities, but also to live out relationships that reflect the character of this divine fellowship. Missiologically, this understanding implies that the contemporary church needs to actualize its calling both relationally and contextually, especially in facing the increasingly plural and dynamic realities of society.